Immunohistochemical Localization of a Novel Peptide, Prostacyclin-Stimulating Factor (PSF), in Human Tissues - Masakado, Mitsunorl; Umeda, Fumio; Takei, Akira; Hashimoto, Toshihiko; Suelshi, Katsuo; Nawata, Hajime (Thrombosis and Haemostasis, 1995)
In a recent study, we purified and cloned a newly identified bioactive factor that stimulates prostacyclin (PGI2) production by vascular endothelial cells (ECs) using conditioned medium (CM) from cultured human diploid fibroblast cells. The present study was undertaken to clarify whether PSF is expressed in ECs and vascular smooth muscle cells (SMCs) of human tissues at a protein level. In an immunohistochemical study of seven human autopsy cases, all arteries in all lungs (n = 4) and kidneys (n = 6) examined stained positive to variable extents for PGI2-stimulating factor (PSF). PSF was predominantly expressed by SMCs in the media of small arteries. Staining for PSF was weaker in SMCs of aortic media (n = 3) and strong in SMCs of vaso vasorum (n = 3). PSF staining was also found in the SMCs of human bronchi (n = 4). Immunoblot analysis confirmed that PSF is present in CM from cultured bovine aortic SMCs.